The Koran : a very short introduction - Cook, Michael (Oxford University Press, 2000)
The Koran has constituted a remarkably strong core of identity and continuity for a religious tradition that is now in its fifteenth century. This Very Short Introduction explores the significance of the Koran both in the modern world and in traditional Muslim culture. Michael Cook provides a lucid and direct account of the Koran as codex, as scripture, as liturgy, and as the embodiment of truth, and examines its means of formation and dissemination. He also discusses issues of interpretation for certain key verses, demonstrating that fecundity of the text for readers throughout the world.